Identification of Secondary Metabolites from Ethanol Extract of Ciplukan (Physalis angulate) Leaves and Toxicity Test on Post-Larvae of Tiger Shrimp (Penaeus monodon) [Identifikasi Senyawa Metabolit Sekunder Ektrak Etanol Daun Ciplukan (Physalis angulata) dan Uji Toksisitas terhadap Sintasan Post Larva Udang Windu (Penaeus monodon)] - Awaludin Awaludin; Yulma Yulma (Jurnal Ilmiah Perikanan dan Kelautan)
Abstract Physalis angulata is a garden plant that has been widely used as a medicinal plant by the community. This plant contains secondary metabolites that can be used as medicine and nutrition enhancement. This study aims to identify the secondary metabolite compounds and their toxicity to the post-larva (PL) survival rate in tiger prawns. This study was conducted in several stages (1). P. angulata extraction using ethanol, (2) P. angulata GCMS test, (3) The identification of the secondary metabolites from P. angulata (4) LC50 test (Lethal Concentration 50) and (5) Data analysis. Based on the results of GCMS analysis, it was indicated that P. angulata contained the secondary metabolite compounds, including phenols, steroids, fatty acids, terpenoids, benzenes, and alkaloids. It is concluded that the compounds contained are presumed to be beneficial for prawn farming development in terms of disease prevention, growth acceleration, and egg quality improvement. Meanwhile, the toxicity test results by using tiger prawn larvae for 48 hours revealed that the safe concentration level used for prawn development by utilizing the cutleaf groundcherry extract was at 13.1 mg/l.